Negative Correlation Between 18F-RGD Uptake via PET and Tumoral PD-L1 Expression in Non-Small Cell Lung Cancer - Wu, Leilei; Liu, Jingru; Wang, Shasha; Bai, Menglin; Wu, Min; Gao, Zhenhua; Li, Jianing; Yu, Jinming; Liu, Jie; Meng, Xue (Frontiers in Endocrinology, 2022)
Purpose We investigated the correlation of 18F-AlF-NOTAPRGD2 (18F-RGD) uptake during positron emission tomography (PET) with tumoral programmed death-ligand 1 (PD-L1) expression and explored its potential in immune checkpoint inhibitor treatment. Methods Forty-two mice were subcutaneously injected with CMT-167 lung carcinoma cells. A total of 30 mice with good growth tumor and good general condition were selected. 18F-RGD PET scanning was performed on days 0, 2, 4, 6, 9, and 11 with five mice per day. Immunohistochemistry (IHC) for PD-L1 was performed on each specimen obtained from tumors. Thirty patients with advanced non-small cell lung cancer (NSCLC) were scanned using 18F-RGD PET/CT, and Milliplex multifactor detection analyzed serum PD-1/PD-L1 expression of twenty-eight of them. Thirteen of them were analyzed immunohistochemically using core needle biopsy samples obtained from primary tumors. Results Thirty mice were scanned by 18F-RGD PET/CT and analyzed for PD-L1 expression in tumor cells by IHC finally. Maximum standard uptake value (SUVmax) and mean SUV (SUVmean) were significantly lower in relatively-higher-PD-L1-expression tumors than in relatively-low-PD-L1-expression tumors (P < 0.05). In patients, the SUVmax was significantly negatively correlated with tumoral PD-L1 expression by IHC (P=0.014). SUVmean, peak SUV (SUVpeak), and gross tumor volume (GTV) were also negatively correlated with PD-L1, but without significance (P > 0.05). SUVmax, SUVmean, SUVpeak, and GTV were negatively correlated with serum PD-1 and PD-L1, but not significantly. According to the receiver operating characteristic curve analysis, significant correlations between SUVmax and tumoral PD-L1 expression in both mice and patients were present (P < 0.05). Conclusion Higher 18F-RGD uptake is correlated with depressed PD-L1 expression in tumor cells, and SUVmax is the best parameter to display tumoral expression of PD-L1. 18F-RGD PET may be useful for reflecting the immune status of NSCLC.